Establishment of a pop-up library as an extension service of a public library - Talag, Rima Paulyn E.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Public libraries are an essential part of every city, it is known to contribute greatly to the knowledge and skills of a community. In the Philippines, as of 2008, there are a total of 1157 public libraries around the country. This is supported by the Republic Act 7743 implemented in 1994, that dictates that public libraries in the Philippines are a must and that its main role is to improve literacy in the country.

This research focused on creating a platform to bring the Pasig City Public Library to the community through the construction of a Pop-up Library in Barangay Kapitolyo. A pop-up library is often associated and seen as similar with a mobile library, but instead of being in a vehicle and mobile it is set-up in a permanent location for a specific period of time. The FREE: Finding Readers to Educate and Enjoy, pop-up library was set-up in front of a popular food park in Barangay Kapitolyo Pasig City.

The researcher interviewed patrons who approached and stopped by. Responses gathered presented that there is a lack of awareness in both Public and Pop-up libraries. Positive receptions were the majority of feedbacks attained from the patrons. A pop-up library is an effective way to introduce the facilities and services of a public library.
Thesis (Bachelor of Library and Information Science)
Keywords: Pasig City Public Library; Young adults' libraries -- Activity programs; Republic Act 7743.; RA 7743.